HRDQ Section Sarawak Timber Industry Development Corporation (STIDC) Wisma Sumber Alam, Jalan Stadium, Petra Jaya, 93050 Kuching, Sarawak / Ahmad Zamri Kemeri - Kemeri, Ahmad Zamri (Universiti Teknologi MARA, Sarawak, 2015)
Industrial Training is for student doing in their practical. This is a big opportunity for us to learn how to be independent during working. We can study a lot about environment during working. Try to adapt how their working and learn how to be more creative and be more proactive. Sarawak Timber Industry Development Corporation (STIDC) is a big corporation and their are always dealing with outsider people. When first I came here, of course I feel nervous and excited to do a practical. As I am, this is my first experience working and this is the first I work alone without my friends. Since I being here, Sarawak Timber Industry Development Corporation (STIDC) is the best company I have ever seen. For that reason, they as employees there are very tolerant, collaborating in groups, friendly and integrity. By each section, they would hold a forum, seminar or talk. We as practical students, highly encouraged to attend any forum or seminar so that we as students are active in practically any activity at PUSAKA. End of each month, PUSAKA will hold a assembly at the seminar hall at the end of each month and with it all the employees in the PUSAKA highly encouraged to attend the assembly. The same goes with practical students, they are also encouraged to attend the assembly every end of each month. We as practical students must active in any activity at PUSAKA so that they know we as practical student are active and easy to be friend, also mild bone to help each other. Other than that, we have to respect them because we just practical in this company so people always watching our behaviour and our movement if we be more friendly and always respect people, they will like us and we have a good respond from them and our manager also will like us.